Extracellular Matrix Degradation - Parks, William C.; Mecham, Robert P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Regulated turnover of extracellular matrix (ECM) is an important component of tissue homeostasis. In recent years, the enzymes that participate in, and control ECM turnover have been the focus of research that touches on development, tissue remodeling, inflammation and disease. This volume in the Biology of Extracellular Matrix series provides a review of the known classes of proteases that degrade ECM both outside and inside the cell. The specific EMC proteases that are discussed include cathepsins, bacterial collagenases, matrix metalloproteinases, meprins, serine proteases, and elastases. The volume also discusses the domains responsible for specific biochemical characteristics of the proteases and the physical interactions that occur when the protease interacts with substrate. The topics covered in this volume provide an important context for understanding the role that matrix-degrading proteases play in normal tissue remodeling and in diseases such as cancer and lung disease. The series Biology of Extracellular Matrix is published in collaboration with the American Society for Matrix Biology.
Matrix Metalloproteinases and Their Inhibitors in Turnover and Degradation of Extracellular Matrix -- Role of Cysteine Cathepsins in Extracellular Proteolysis -- Cooperation between proteolysis and endocytosis in collagen turnover -- Pericellular Proteolysis -- Triple Helicase Activity and the Structural Basis of Collagenolysis -- Structural Basis of Extracellular Matrix Interactions with Matrix Metalloproteinases -- The Role of Matrix Metalloproteinases in Cellular Invasion and Metastasis -- Degradation of bone and the role of osteoclasts, bone lining cells and osteocytes -- Consequences of Elastolysis.
Keywords: Life sciences; Medicine; Biochemistry; Cytology; Life Sciences; Cell Biology; Biochemistry, general; Protein Science; Molecular Medicine